HGG-02. EXTRACRANIAL METASTASIS OF GLIOBLASTOMA- - A REPORT OF THREE PEDIATRIC PATIENTS. Issue 2 (22nd June 2018) - Greer, Chelsee; Harrod, Virginia; Krishnan, Chandra; George, Timothy
Abstract: Extracranial metastasis of glioblastoma is an exceedingly rare event and is thought to be present in less than 2% of cases. Review of the literature yields few case reports with regards to the pediatric population over a lengthy time frame. Here, we describe three cases over the last six years of pediatric extracranial metastasis in glioblastoma patients. All patients were male with age ranging from 7 month to 12 years old. They were treated similarly with small variations in maintenance therapy. Time to extracranial metastasis varied between 6-23 months. One patient had a ventriculoperitoneal (VP) shunt in place prior to extracranial metastasis. Extracranial metastasis were in bone (n=2) and liver (n=1). All patients died of disease within 3-6 weeks after extracranial metastatic disease was first noted. This data suggests that new life-prolonging treatment strategies in glioblastoma are possibly leading to extended life and increased incidence of extracranial disease spread. Genomic analysis of subclassification of tumors may give insight into subtypes of glioblastoma likely to spread outside the CNS. This may aid in future strategies for treatment and possible increased imaging surveillance in a subset of patients.